Effect of surface treatment and particle loading on the mechanical properties of CFB fly ash reinforced thermoset composite - Reyes, Joy Erika P. (College of Engineering, University of the Philippines Diliman, 2014)
Circulating fluidized bed (BFB) boilers, a relatively new and more environment-friendly technology, produce fly ash with limited use on the construction industry. This study focused on the use of CFB fly ash as a filter material in thermoset composites. CFB fly ash was treated with coconut oil using the procedure used by Yao et.al. (2013). The fly ash was applied to orthophthalic unsaturated polyester resin at different particle loading. The untreated and treated fly ash were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray fluorescence (XRF). Tensile and flexural properties of composites with varying fly ash loading were measured using universal testing machine (UTM). The tensile and flexural modulus increased while the tensile and flexural decreased with increasing particle loading. Improvement in the mechanical properties of the composites with treated fly ash relative to the ones with the untreated was observed. This is caused by enhanced particle-matrix adhesion and improved particle dispersion. Moisture absorption caused a decline in the flexural properties of the composites. Water acted as a plasticizer so the matrix weakened upon immersion.